The Mediating Role of Math Anxiety in the Relationship Between Self-Concept and Resilience Among Elementary School Students - Afra Munifah; Olivia Amelizky; Suci Nurhayati (CV. Akademi Merdeka, 2025)
Learning mathematics in elementary school often causes anxiety in students, which has an impact on their low self-concept and resilience in solving problems. This study aims to examine the mediating role of anxiety on the relationship between self-concept and resilience in learning mathematics in elementary school students. This study used a quantitative research type of non-experimental design survey method. The research sample consisted of 260 elementary school students in grades 3 and 4 who were purposively selected. Data were collected through a scale questionnaire of self-concept, math anxiety, and student resilience. The data analysis technique used was path analysis with the help of SmartPLS 4 software. The results showed that there was a negative relationship between self-concept and anxiety, as well as a positive relationship between self-concept and resilience. Anxiety mediates the relationship between self-concept and student resilience. This study highlight the critical role on affective factors in mathematics learning at the primary school level. The findings are significant for the development of educational interventions that emphasize strengthening self-concept and reducing anxiety to enhance students' future learning resilience.